Walizka z bibułkami. Edycja Paryża ze złota… Leo Lipskiego - Gosk, Hanna (Narracje o Zagładzie, 2017)
A Suitcase Full of Manifold Paper. On Editing Leo Lipski’s Paryż ze złota… This article is an account of the “adventure” of editing Leo Lipski’s texts, be it memoirs, and epistolary and poetic forms, which are stored in his “archive” in Tel Aviv, preserved and controlled by Łucja Gliksman, a long‑time friend of his. The material collected was eventually published by Świat Literacki as Paryż ze złota. Teksty rozproszone in 2002. The aforementioned “archive” has been stored in a worn‑out, small suitcase full of undated and nearly illegible texts typed many years before by means of the manifold paper – a faded yellowish one, or, to be precise, its snippets. Therefore, the whole task of wading through them and selecting those deserving greater attention was extremely difficult. Yet another obstacle was Łucja Gliksman herself who simultaneously allowed the editor to finish her work properly and was deciding upon erasing particular content in the book in an autocratic manner, based often on her private and intimate motivation. The article is concluded with a reflection upon the uneasy task of negotiating with the right‑holders of the dead writers’ works. Key words: Leo Lipski, Łucja Gliksman, editing, Paryż ze złota…